Hybrid Interactive Multimedia Learning with Mixed Reality (A Case Study of Visual Communication Design Course at UMT) - Aliyah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Learning visual communication design lectures using Mixed Reality with Hololens glasses that display Motion, Image Graphics, and interesting lecture interests, Mixed Reality method-based technology, a combination of Augmented Reality and Virtual Reality, a blend of the virtual world with the real world. This innovation is the answer to the recent transition from pandemic to normal, increasing the attractiveness and enthusiasm of students in lecture activities that are used to being passive begin to become active again. The use of Mixed Reality requires MR Box Hololens hardware support. With the Mixed Reality application, 3D designs and animations look more alive and from semi-real to real. The method used in this study is a qualitative research method, which describes how the manufacturing process reaches its destination. The development of learning with Mixed Reality is by following the Visual Communication Design study program, gives students a persuasive and, overview of the all designs.